Traditional Chinese Medicine for Coronary Artery Disease Treatment: Clinical Evidence From Randomized Controlled Trials - Liang, Bo; Gu, Ning (Frontiers in Cardiovascular Medicine, 2021)
Traditional Chinese medicine has a history of more than 2,000 years and has been widely used in clinical practice. However, due to the lack of a reliable scientific basis, the role of traditional Chinese medicine in the prevention and treatment of coronary artery disease is not clear. At present, the existing randomized controlled trials about traditional Chinese medicine for coronary artery disease have defects, small sample sizes, and different results, so it is difficult to make a clear conclusion on the actual advantages and disadvantages of traditional Chinese medicine. In this review, the efficacy and safety of traditional Chinese medicine in the prevention and treatment of coronary artery disease were systematically evaluated through randomized controlled trials, most of which were double-blind trials. We reviewed 17 randomized controlled trials that included a total of 11,726 coronary artery disease patients. The methodological quality of the trials was generally high, with nine (52.94%) having a modified Jadad score of 7 and only three (17.65%) having a modified Jadad score of <3. There are 16 trials (94.12%) reporting safety; the safety of traditional Chinese medicine seems not to be inferior to that of mimetic, placebo, or western medications. Moreover, the results from 17 randomized controlled trials (100.00%) showed that traditional Chinese medicine can be applied as a complementary and alternative method to the primary and secondary prevention of coronary artery disease, and only six trials (35.29%) described adverse cardiovascular events specifically. However, it is necessary to assess the safety and efficacy of traditional Chinese medicine in treating coronary artery disease with long-term hard endpoints.